2019
DOI: 10.1186/s13293-019-0227-9
|View full text |Cite
|
Sign up to set email alerts
|

X-chromosome association study reveals genetic susceptibility loci of nasopharyngeal carcinoma

Abstract: BackgroundThe male predominance in the incidence of nasopharyngeal carcinoma (NPC) suggests the contribution of the X chromosome to the susceptibility of NPC. However, no X-linked susceptibility loci have been examined by genome-wide association studies (GWASs) for NPC by far.MethodsTo understand the contribution of the X chromosome in NPC susceptibility, we conducted an X chromosome-wide association analysis on 1615 NPC patients and 1025 healthy controls of Guangdong Chinese, followed by two validation analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Its incidence is highest among males and its occurrence is particularly frequent in China. An X chromosome-wide association study for SNPs in 1590 Chinese NPC patients and 994 controls revealed an association within the DMD gene (intronic SNP rs5927056, p = 1.49 × 10 − 5 ), which was validated in Taiwanese and Malaysian replication cohorts [ 26 ]. Combination analyses revealed a consistent association in males and showed that the DMD SNP rs5927056 is associated with a reduced risk of NPC (odds ratio: 0.85, p = 9.44 × 10 − 5 ) [ 26 ].…”
Section: Carcinomasmentioning
confidence: 99%
See 3 more Smart Citations
“…Its incidence is highest among males and its occurrence is particularly frequent in China. An X chromosome-wide association study for SNPs in 1590 Chinese NPC patients and 994 controls revealed an association within the DMD gene (intronic SNP rs5927056, p = 1.49 × 10 − 5 ), which was validated in Taiwanese and Malaysian replication cohorts [ 26 ]. Combination analyses revealed a consistent association in males and showed that the DMD SNP rs5927056 is associated with a reduced risk of NPC (odds ratio: 0.85, p = 9.44 × 10 − 5 ) [ 26 ].…”
Section: Carcinomasmentioning
confidence: 99%
“…An X chromosome-wide association study for SNPs in 1590 Chinese NPC patients and 994 controls revealed an association within the DMD gene (intronic SNP rs5927056, p = 1.49 × 10 − 5 ), which was validated in Taiwanese and Malaysian replication cohorts [ 26 ]. Combination analyses revealed a consistent association in males and showed that the DMD SNP rs5927056 is associated with a reduced risk of NPC (odds ratio: 0.85, p = 9.44 × 10 − 5 ) [ 26 ]. Additionally, NPC risk association with X chromosome SNPs was found to be decreased by 8.3% after excluding rs5927056, suggesting a strong effect of this locus on NPC susceptibility.…”
Section: Carcinomasmentioning
confidence: 99%
See 2 more Smart Citations
“…Nasopharyngeal carcinoma (NPC), an epithelial malignancy, is related to Epstein–Barr virus infection [ 1 ]. The pathogenesis of NPC is multifactorial, such as genetic susceptibility [ 2 ], social practices, and environmental factors [ 3 , 4 ]. NPC is frequent in southern China and Southeast Asia with an incidence of 40 cases per 1,00,000 individuals yearly; however, it is infrequent in Western Europe and North America [ 5 ].…”
Section: Introductionmentioning
confidence: 99%